Is higher body temperature beneficial in ischemic stroke patients with normal admission CT angiography of the cerebral arteries? - Kvistad CE (Vascular Health and Risk Management, 2014)
Christopher Elnan Kvistad,1 Andrej Khanevski,1 Aliona Nacu,1 Lars Thomassen,1 Ulrike Waje-Andreassen,1 Halvor Naess1,2 1Department of Neurology, Haukeland University Hospital, Bergen, Norway; 2Centre for Age-related Medicine, Stavanger University Hospital, Stavanger, NorwayBackground: Low body temperature is considered beneficial in ischemic stroke due to neuroprotective mechanisms, yet some studies suggest that higher temperatures may improve clot lysis and outcomes in stroke patients treated with tissue plasminogen activator (tPA). The effect of increased body temperature in stroke patients treated with tPA and with normal computed tomography angiography (CTA) on admission is unknown. We hypothesized a beneficial effect of higher body temperature in the absence of visible clots on CTA, possibly due to enhanced lysis of small, peripheral clots.Methods: Patients with ischemic stroke admitted to our Stroke Unit between February 2006 and April 2013 were prospectively registered in a database (Bergen NORSTROKE Registry). Ischemic stroke patients treated with tPA with normal CTA of the cerebral arteries were included. Outcomes were assessed by the modified Rankin Scale (mRS) after 1 week. An excellent outcome was defined as mRS=0, and a favorable outcome as mRS=0–1.Results: A total of 172 patients were included, of which 48 (27.9%) had an admission body temperature ≥37.0°C, and 124 (72.1%) had a body temperature <37.0°C. Body temperature ≥37.0°C was independently associated with excellent outcomes (odds ratio [OR]: 2.8; 95% confidence interval [CI]: 1.24–6.46; P=0.014) and favorable outcomes (OR: 2.8; 95% CI: 1.13–4.98; P=0.015) when adjusted for confounders.Conclusion: We found an association between higher admission body temperature and improved outcome in tPA-treated stroke patients with normal admission CTA of the cerebral arteries. This may suggest a beneficial effect of higher body temperature on clot lysis in the absence of visible clots on CTA.Keywords: acute ischemic stroke, body temperature, thrombolysis, tissue plasminogen activator